Análise de taxa média de bloqueio em conexões por algoritmos de caminhos mínimos: algoritmo de Yen e algoritmo genético - Barreto, Tarcisio da Silva (2014)
Studies on connections lock in computer networks have been gaining prominence in recent research focused on computational communication and technology. Several researchers have used various methods in order to identify and minimize the blocking rate that prevent a connection is established. This paper presents a blocking rate analysis in connections of shortest paths algorithms. They have on the performance of a transparent optical network. Two algorithms will be used to perform the analysis and simulations, the Genetic Algorithm (AG) and the algorithm Yen (AY). The Genetic Algorithm is based on Computational Intelligence (CI) and the Yen algorithm is based on the principle of finding and identifying the K shortest paths. Numerical simulations performed on different network scenarios show that the greater the number of connections, the higher the blocking rate in the connections. This study will help to identify which algorithm behaves better in the specific cases described in this work